INDONESIA, NASIONALISME, DAN INGATAN KOLEKTIF: MENGEMBANGKAN NASIONALISME INDONESIA MELALUI PENEGASAN INGATAN KOLEKTIF - Wattimena, Reza A. A. (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2009)
The crisis of nationalism is one of many social problems faced by Indonesian people today. From the theoretical perspective, the sign of the crisis can be seen in the absence of significant political movement and public will to achieve the ideal of the nation, as it is written in the Indonesian constitution. This paper suggests that the crisis can be overcome if a strong social identity can be constructed based on meaningful collective memory. The analysis is based on the concept of nationalism of Ernst Gellner and Wayne Norman, connected to the thoughts of Maurice Halbwachs. The discussion will end up with its application in Indonesian context.